ANALISA KEPATUHAN PENGGUNAAN DOSE CONSTRAINT DI INSTALASI RADIOLOGI RUMAH SAKIT SEBAGAI IMPLEMENTASI ASAS OPTIMISASI DALAM KESELAMATAN RADIASI - Maizza Nadia Putri; Agi Febrian Trihadijaya; Talitha Arabella Hanum (Perhimpunan Radiografer Indonesia (PARI), 2023)
ABSTRACT Background: No data has yet been found regarding the evaluation of the use of Dose Constraints in a hospital radiology installation. The purpose of this study was to determine the percentage of adherence to the use of dose constraints in a radiology installation as well as analysis and follow-up. Methods: The research was conducted by making observations at 30 Hospitals on the island of Java, the researchers distributed a questionnaire survey in the form of 20 data using the exposure factor for Thorax PA examination which would then be inputted through the Si-INTAN application to obtain ESAK values. Results: Based on 600 data on the use of exposure factors from 30 samples of hospitals on the island of Java, it was found that 21 or 70% of the hospitals adhered to the use of dose constraints and as many as 9 or 30% of hospitals do not comply with the use of the determined dose constraint. Conclusions: Of the 9 hospitals that were not compliant with the use of the dose constraint, the highest ESAK value was obtained from RS-18, which was 0.939 mGy, which reached twice the stipulated I-DRL Thorax examination value. It can be seen that these hospitals used the most mAs. higher than other hospitals. The mAs values used range from 10-28 mAs. When compared with the lowest ESAK value, namely RS-3, it only uses 5 mAs for an adult thorax examination. to suppress ESAK doses to be lower we can use high tube voltages. to obtain an exposure with the same transmission at a patient thickness of 20 cm, namely by increasing one of the irradiation parameters of the tube voltage value by compensating for a decrease in the tube current-time value to produce an image density that is almost the same,and using very low mAs also results in a dose radiation is very small.